The Global Budget of Atmospheric Methanol: New Constraints on Secondary, Oceanic, and Terrestrial Sources. Issue 4 (22nd February 2021) - Bates, Kelvin H.; Jacob, Daniel J.; Wang, Siyuan; Hornbrook, Rebecca S.; Apel, Eric C.; Kim, Michelle J.; Millet, Dylan B.; Wells, Kelley C.; Chen, Xin; Brewer, Jared F.; Ray, Eric A.; Commane, Róisín; et al.
Abstract: Methanol is the second‐most abundant organic gas in the remote atmosphere after methane, but its sources are poorly understood. Here, we report a global budget of methanol constrained by observations from the ATom aircraft campaign as implemented in the GEOS‐Chem global atmospheric chemistry model. ATom observations under background marine conditions can be fit in the model with a surface ocean methanol concentration of 61 nM and a methanol yield of 13% from the newly implemented CH3 O2 + OH reaction. While terrestrial biogenic emissions dominate the global atmospheric methanol budget, secondary production from CH3 O2 + OH and CH3 O2 + CH3 O2 accounts for 29% of the total methanol source, and makes up the majority of methanol in the background marine atmosphere sampled by ATom. Net emission from the ocean is comparatively minor, particularly because of rapid deposition from the marine boundary layer. Aged anthropogenic and pyrogenic plumes sampled in ATom featured large methanol enhancements to constrain the corresponding sources. Methanol enhancements in pyrogenic plumes did not decay with age, implying in‐plume secondary production. The atmospheric lifetime of methanol is only 5.3 days, reflecting losses of comparable magnitude from photooxidation and deposition. GEOS‐Chem model results indicate that methanol photochemistry contributes 5%, 4%, and 1.5% of the tropospheric burdens of formaldehyde, CO, and ozone, respectively, with particularly pronounced effects in the tropical upper troposphere. The CH3 O2 + OH reaction has substantial impacts on radical budgets throughout the troposphere and should be included in global atmospheric chemistry models. Plain Language Summary: Methanol is the most abundant nonmethane organic gas in the lower atmosphere, but the magnitudes of its sources and sinks remain uncertain. Here, we evaluate a global atmospheric chemistry model against recent observations of methanol in the remote atmosphere to better constrain the methanol budget. We show that, relative to past studies, the new data suggest a smaller atmospheric methanol source from the ocean and a larger source from gas‐phase chemistry. Methanol emitted from the oceans plays a particularly small role in the atmosphere because it is quickly deposited back to the ocean surface. We incorporate these updates into the global model and evaluate their importance for atmospheric chemistry more broadly, showing that methanol directly and indirectly influences the abundances of many other tropospheric trace gases. Key Points: Chemical production is the dominant source of background methanol in the remote troposphere The ocean is a net sink of atmospheric methanol and provides only a minor methanol source to the marine boundary layer The CH3 O2 + OH reaction plays a key role in the atmospheric budgets not only of methanol but of many tropospheric radical species